MicroRNA‐148a‐3p inhibited the proliferation and epithelial–mesenchymal transition progression of non‐small‐cell lung cancer via modulating Ras/MAPK/Erk signaling. Issue 8 (10th December 2018) - Xie, Qiong; Yu, Zipu; Lu, Yuan; Fan, Jingya; Ni, Yiming; Ma, Liang
Abstract: Son of sevenless (SOS) is one of the guanine nucleotide exchange factors that can regulate the mitogen‐activated protein kinase/extracellular signal regulated kinase signal pathway via controlling the activation of Ras. microRNAs are key regulon of gene expression and would be treated as tumor biomarkers or therapeutic targets. In this study, we find that miR‐148a‐3p acts as a tumor‐suppressor in the development and progression of non‐small‐cell lung cancer (NSCLC). miR‐148a‐3p inhibits NSCLC cells proliferation and epithelial–mesenchymal transition by reducing the expression of SOS2, which refers Ras activating. Our findings demonstrate that the miR‐148a‐3p may play a significant role in NSCLC including the kind of lung cancer with K‐Ras gene mutation, and it exerted the tumor inhibitor function by targeting SOS2. Because of that, miR‐148a‐3p and SOS2 may be an efficient target in developing more useful therapies against NSCLC. Abstract : miR‐148a‐3p is downregulated in non‐small‐cell lung cancer (NSCLC) cells, and overexpression of miR‐148a‐3p inhibits the proliferation and the motility of NSCLC cells. miR‐148a‐3p inhibited the proliferation and epithelial–mesenchymal transition progression of NSCLC via targeting SOS2. SOS2 modulates Ras/MAPK/ERK signaling by controlling activation of Ras.